Development of instruments to measure the quality of breast cancer treatment decisions - Lee, Clara N. (Blackwell Publishing Ltd, 2010)
Background  Women with early‐stage breast cancer face a multitude of decisions. The quality of a decision can be measured by the extent to which the treatment reflects what is most important to an informed patient. Reliable and valid measures of patients’ knowledge and their goals and concerns related to breast cancer treatments are needed to assess the decision quality. Objective  To identify a set of key facts and goals relevant to each of three breast cancer treatment decisions (surgery, reconstruction and adjuvant chemotherapy and hormone therapy) and to evaluate the validity of the methods used to identify them. Methods  Candidate facts and goals were chosen based on evidence review and qualitative studies with breast cancer patients and providers. Cross‐sectional surveys of patients and providers were conducted for each decision. The accuracy, importance and completeness of the items were examined. Results  Thirty‐eight facts (11–14 per decision) and 27 goals (8–10 per decision) were identified. An average of 17 patients and 21 providers responded to each survey. The sets of facts were accurate and complete for all three decisions. The sets of goals and concerns were important for surgery and reconstruction, but not chemotherapy/hormone therapy. Patients and providers disagreed about the relative importance of several key facts and goals. Conclusions  Overall, breast cancer patients and providers found the sets of facts and goals accurate, important and complete for three treatment decisions. Because patients’ and providers’ perspectives are different, it is vital that instrument development should include items reflecting both views.